Urbanization in Archaeological Interpretation. Case study: "Hellenized settlements" in the Central Balkans - Ivan Vranić (University of Belgrade, 2016)
In the archaeological literature, the problem of urbanization and the emergence of cities have most often been solved in the framework of the formation of states and first "civilizations". Both in traditional and more recent works based on evolutionary theory, it has been presupposed that these are the settlements of the communities on the "state level", with fully developed complex society. Evolutionary theory, as an Eurocentric approach, is frequently present in the archaeology of the Balkans, used as a tool in the classification of settlements and identification of cities, thus leading to the practice of evaluation of heritage as "better" or "more advanced". The paper examines the problem of urbanization from two theoretical starting points, focusing on the case study of the so-called "Hellenized settlements" of the Balkan Iron Age. The first line of inquiry is based upon the contemporary evolutionary theory, taking into account the post-modern critique of the approach. The conclusion is that the Iron Age communities do not comply with all the characteristic traits of complex societies, raising considerable doubt concerning the interpretation of the settlements as cities. The second part of the paper examines the issue of heritage and its active role in the modern world, aiming to explain the reasons for the widely accepted interpretation of the Iron Age settlements as urbanized.